Eksplorasi Hierarki Kebutuhan Abraham Maslow dalam Serial Novel Dear Allah Karya Diana Febiantria - Santi Oktaviani; Madania Khalifah; Rokiah Rokiah; Agik Nur Efendi (JENTERA: Jurnal Kajian Sastra, 2024)
Literary works are a reflection of the nature of society in real life that the author modifies through imaginative power. Writers often raise humanistic issues in literary works. Maslow's humanism illustrates that every individual needs aspects of physical and psychological needs. The novel Dear Allah tells the problem of phenomena that often occur in households, families, friendships, and friendships. This study aims to explore Maslow's hierarchical needs of the main and supporting characters in the Dear Allah novel series. This research uses descriptive qualitative method. The data source in this study is the Dear Allah novel series in the romance genre published in 2018 and 2022. Data collection techniques were carried out by reading the Dear Allah novel series, creating an analysis table, determining Maslow's hierarchy of needs, grouping data based on analysis criteria, and entering into the analysis table. Data analysis techniques include data reduction, data presentation, and conclusion drawing. Based on the results and discussion, it shows that the characters Naira, Wildan, and Silla succeeded in fulfilling Maslow's hierarchy of needs from the physiological level to self-actualization, such as financial stability, love, and self-acceptance. In contrast, Zulfa fails to achieve her need for security due to emotional and physical conflicts, while Genta achieves self-actualization through the acceptance of unrequited love. The whole story reflects the characters' psychological journey in fulfilling their basic to highest needs according to Maslow's theory. AbstrakKarya sastra merupakan cerminan dari sifat masyarakat dalam kehidupan nyata yang dimodifikasi penulis melalui daya imajinatif. Penulis seringkali mengangkat isu humanistik di dalam karya sastra. Humanistik Maslow memberikan gambaran bahwa setiap individu membutuhkan aspek kebutuhan fisik dan psikis.Novel Dear Allah menceritakan problematika mengenai fenomena yang sering terjadi dalammahligai rumah tangga, keluarga, persahabatan, dan pertemanan. Penelitian ini bertujuan untuk mengeksplorasi kebutuhan hierarki Maslow pada tokoh utama dan pendukung dalam serial novel Dear Allah. Penelitian ini menggunakan metode kualitatif deskriptif. Sumber data dalam penelitian ini adalah serial novel Dear Allah bergenre romantisme terbitan tahun 2018 dan 2022. Teknik pengumpulan data dilakukan dengan membaca serial novel Dear Allah, membuat tabel analisis, menentukan hierarki kebutuhan Maslow, mengelompokkan data berdasarkan kriteria analisis, dan memasukkan ke dalam tabel analisis. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil dan pembahasan yang dilakukan menunjukkan bahwa tokoh Naira, Wildan, dan Silla berhasil memenuhi kebutuhan hierarki Maslow dari tingkat fisiologis hingga aktualisasi diri, seperti stabilitas finansial, cinta, dan penerimaan diri. Sebaliknya, tokoh Zulfa gagal mencapai kebutuhan rasa aman karena konflik emosional dan fisik, sementara Genta mencapai aktualisasi diri melalui penerimaan cinta yang tidak terbalas. Keseluruhan cerita mencerminkan perjalanan psikologis tokoh dalam memenuhi kebutuhan dasar hingga tertinggi sesuai teori Maslow.